Data integration and participatory process in developing integrated coastal zone management (ICZM) in the northern Baltic Sea - Hietala Reija; Ijäs Asko; Pikner Tarmo; Kull Anne; Printsmann Anu; Kuusik Maila; Fagerholm Nora; Vihervaara Petteri; Nordström Paulina; Kostamo Kirsi (Springer, 2022)
The Maritime Spatial Planning (MSP) Directive was ratifed (2014/89/EU) along the Strategy of the European Union (EU) on the Blue Economy to contribute to the efective management of maritime activities and resources and incorporate the principal elements of Integrated Coastal Zone Management (ICZM) (2002/413/EC) into planning at the land-sea interface. There is a need to develop the ICZM approach throughout Europe to realise the potential for both socio-economic and environmental targets set by the EU and national legislations. In this study, we co-developed diferent approaches for land-sea interactions in four case areas in Estonia and Finland based on the defned characteristics and key interests derived from local or regional challenges by integrating spatial data on human activities and ecology. Furthermore, four ICZM drafts were co-evaluated by stakeholders and the public using online map-based assessment tools (public participatory GIS). The ICZM approaches of the Estonian cases ranged from the diversifcation of land use to the enhancement of community-based entrepreneurship. The Finnish cases aimed to defne the trends for sustainable marine and coastal tourism and introduce the ecosystem service concept in land use planning. During the project activities, we found that increased communication and exchange of local and regional views and values on the prevailing land-sea interactions were important for the entire process. Thereafter, the ICZM plans were applied to the MSP processes nationally, and they support the sustainable development of coastal areas in Estonia and Finland.